2017
DOI: 10.1002/pros.23392
|View full text |Cite
|
Sign up to set email alerts
|

Insight into infection‐mediated prostate damage: Contrasting patterns of C‐reactive protein and prostate‐specific antigen levels during infection

Abstract: Background To investigate mechanisms underlying our previous observation of a large rise in serum prostate-specific antigen, a marker of prostate pathology, during both sexually transmitted and systemic infections, we measured serum high-sensitivity C-reactive protein (hsCRP), a marker of systemic inflammation, in our previous case-control study of young, male U.S. military members and compared our findings to those for PSA. Methods We measured hsCRP before and during infection for 299 chlamydia, 112 gonorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In our previous study of young US military members, we found that serum PSA rose during episodes of adult-onset infectious mononucleosis (IM) and other systemic infections, 3 and remained higher than their baseline concentrations even after levels of high sensitivity C-reactive protein, a marker of systemic inflammation, fell. 9 Elevated PSA concentrations were also observed in a case report of a man with Chikungunya virus infection. 10 Together with findings for genitourinary tract infections, these results suggest that many types of infections may influence the prostate, either directly through prostate infection or indirectly through possible mechanisms such as local genitourinary-or systemic inflammation-mediated cell damage, leading to chronic prostate inflammation.…”
mentioning
confidence: 81%
“…In our previous study of young US military members, we found that serum PSA rose during episodes of adult-onset infectious mononucleosis (IM) and other systemic infections, 3 and remained higher than their baseline concentrations even after levels of high sensitivity C-reactive protein, a marker of systemic inflammation, fell. 9 Elevated PSA concentrations were also observed in a case report of a man with Chikungunya virus infection. 10 Together with findings for genitourinary tract infections, these results suggest that many types of infections may influence the prostate, either directly through prostate infection or indirectly through possible mechanisms such as local genitourinary-or systemic inflammation-mediated cell damage, leading to chronic prostate inflammation.…”
mentioning
confidence: 81%
“…Values show a peak in 16 April 2015, which is when the patient had shingles, with return to baseline by 24 May 2016 in the military in the context of sexually transmitted illness and also tested a correlation with PSA. 10 However, the rise in CRP was only significant during gonorrhea compared to controls, and CRP levels correlated poorly with PSA. When faced with an unexplained rise in PSA, clinicians should maintain a high level of vigilance for non-prostate cancer conditions including viral infections that may have resulted in a spurious elevation of PSA in order to avoid subjecting patients to unnecessary investigations, interventions, and psychological distress.…”
Section: Discussionmentioning
confidence: 92%
“…The inflammatory cascade may involve proinflammatory cytokines such as IL‐6 and IL‐8, which have been implicated in benign prostatic hypertrophy (BPH), chronic prostatitis, and prostate cancer development (reviewed in). One study measured the levels of C‐reactive protein (CRP) in young males in the military in the context of sexually transmitted illness and also tested a correlation with PSA . However, the rise in CRP was only significant during gonorrhea compared to controls, and CRP levels correlated poorly with PSA.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the level of high sensitivity C-reactive protein was significantly increased in patients with positive SARS-CoV-2 nucleic acid test. The function of high-sensitivity C-reactive protein is similar to that of traditional C-reactive protein, and its elevated level is one of the manifestations of inflammation [9] .And it has been reported that elevated high-sensitivity C-reactive protein may also be one of the early markers of myocardial injury [10,11] ,which indicates that SARS-CoV-2 infection may cause myocardial injury in patients, although further pathological studies are needed to prove this idea. In addition, we found that compared with the patients with negative nucleic acid test, the patients with positive nucleic acid test had lower platelet count and hematocrit, shorter prothrombin time and longer activated partial thromboplastin time, which indicated that the coagulation function of patients with positive nucleic acid test was damaged by virus infection.…”
Section: Discussionmentioning
confidence: 99%